Recent Progress in Surface Modification of Mg Alloys for Biodegradable Orthopedic Applications - Rahim, Shebeer A.; Joseph, M. A.; Sampath Kumar, T. S.; T, Hanas (Frontiers in Materials, 2022)
The combination of lightweight, strength, biodegradability and biocompatibility of magnesium (Mg) alloys can soon break the paradigm for temporary orthopedic implants. As the fulfillment of Mg-based implants inside the physiological environment depends on the interaction at the tissue-implant interface, surface modification appears to be a more practical approach to control the rapid degradation rate. This article reviews recent progress on surface modification of Mg-based materials to tailor the degradation rate and biocompatibility for orthopedic applications. A critical analysis of the advantages and limitations of the various surface modification techniques employed are also included for easy reference of the readers.